(untitled) (Journal of EAHIL, 2016)
The question of a quality management system implementation as a method of quality control improvement of a medicalÂ library and information centre is examined in this article. The article describes the introduction of a process approachÂ to management and its successful introduction in the Republican Medical Library-Information Centre of the RepublicÂ of Tatarstan, Russian Federation.